Some topologies on the set of lattice regular measures - Panagiotis D. Stratigos (International Journal of Mathematics and Mathematical Sciences)
We consider the general setting of A.D. Alexandroff, namely, an arbitrary set X and an arbitrary lattice of subsets of X, ℒ. 𝒜(ℒ) denotes the algebra of subsets of X generated by ℒ and MR(ℒ) the set of all lattice regular, (finitely additive) measures on 𝒜(ℒ).